Using GRACE Data to Estimate Climate Change Impacts on the Earth’s Moment of Inertia - Ren, Diandong; Hu, Aixue (Frontiers in Earth Science, 2021)
The widely used 15-year Gravity Recovery and Climate Experiment (GRACE) measured mass redistribution shows an increasing trend in the nontidal Earth Moment of Inertia (MOI). Various contributing components are independently evaluated using five high quality atmospheric reanalysis datasets and a novelty numerical modeling system. We found a steady, statistically robust (passed a two-tailed t-test at p=0.04 for dof=15) rate of MOI increase reaching ~11.0×10^27 kg m^2/yr, equivalent to a 11.45 μs /yr increase in length of a day, during 2002-2017. Further analysis suggests that Antarctic Ice Sheet contributes the most, followed by Greenland Ice Sheet, precipitation driven land hydrological cycle, Mountain glaciers, and the fluctuation of atmosphere, in this order. Short-term MOI spikes from the GRACE measurements are mostly associated with great low/mid-latitude earthquakes, fitting closely with the MOI variations from the hydrological cycle. Atmospheric fluctuation contributes the least but has a steady trend of 0.5 μs /yr, with horizontal mass distribution contributes twice as much as the vertical expansion and associated lift of the atmosphere’s center of mass. The latter is a previously overlooked term affecting MOI fluctuation. The contribution to the observed MOI trend from a warming climate likely will persists in the future, due largely to the continuous mass loss from Earth’s ice sheets.